Confidence and Attitudes Toward Osteoarthritis Care Among the Current and Emerging Health Workforce: A Multinational Interprofessional Study - Briggs, AM; Hinman, RS; Darlow, B; Bennell, KL; Leech, M; Pizzari, T; Greig, AM; MacKay, C; Bendrups, A; Larmer, PJ; Francis-Cracknell, A; Houlding, E; et al. (Wiley-Blackwell, 2019)
Objective: To measure confidence and attitudes of the current and emerging interprofessional workforce concerning osteoarthritis (OA) care. Methods: Study design is a multinational (Australia, New Zealand, Canada) cross-sectional survey of clinicians (general practitioners [GPs], GP registrars, primary care nurses, and physiotherapists) and final-year medical and physiotherapy students. GPs and GP registrars were only sampled in Australia/New Zealand and Australia, respectively. The study outcomes are as follows: confidence in OA knowledge and skills (customized instrument), biomedical attitudes to care (Pain Attitudes Beliefs Scale [PABS]), attitudes toward high- and low-value care (customized items), attitudes toward exercise/physical activity (free-text responses). Results: A total of 1886 clinicians and 1161 students responded. Although a number of interprofessional differences were identified, confidence in OA knowledge and skills was consistently greatest among physiotherapists and lowest among nurses (eg, the mean difference [95% confidence interval (CI)] for physiotherapist-nurse analyses were 9.3 [7.7-10.9] for knowledge [scale: 11-55] and 14.6 [12.3-17.0] for skills [scale: 16-80]). Similarly, biomedical attitudes were stronger in nurses compared with physiotherapists (6.9 [5.3-8.4]; scale 10-60) and in medical students compared with physiotherapy students (2.0 [1.3-2.7]). Some clinicians and students agreed that people with OA will ultimately require total joint replacement (7%-19% and 19%-22%, respectively), that arthroscopy is an appropriate intervention for knee OA (18%-36% and 35%-44%), and that magnetic resonance imaging is informative for diagnosis and clinical management of hip/knee OA (8%-61% and 21%-52%). Most agreed (90%-98% and 92%-97%) that exercise is indicated and strongly supported by qualitative data. Conclusion: Workforce capacity building that de-emphasizes biomedical management and promotes high-value first-line care options is needed. Knowledge and skills among physiotherapists support leadership roles in OA care for this discipline.